Effects of choice feeding a completed feed and corn on the performance of broilers - A. H., Ramlah; Halim, A. S. (Asian-Australasian Association of Animal Production Societies, 1994)
Poultry feeding systems are likely to change for increased efficiency of production. An experiment was conducted to compare the response of broilers to choice feeding of corn with a standard broiler ration. The treatments consisted of providing broiler feed as the only feed (SINGLE FEED) and access to corn as a choice to a complete broiler feed (CHOICE FEEDING). Weights and feed consumption were obtained at weekly intervals. Samples at the conclusion of the experiment were taken to determine the weight of abdominal fat. Results showed that there was no significant difference in term of liveweight between the two feeding regimes. However, birds given a choice of the broiler feed and corn had better feed efficiency which is reflected by the lower total feed intake. Corn intake was 23.1% of total feed intake in the choice fed birds. In term of carcass colour, birds fed corn as a choice was observed to have a deeper yellow skin colour than the birds fed with broiler feed only.